A worldly Christian the life and times of Stephen Neill - Daughrity, Dyron B., 1973- (Lutterworth Press, 2021)
Bishop Stephen Neill was one of the most prolific, accomplished, and fascinating Christian leaders of the global church in the twentieth century. Privileged to live in radically different cultural contexts over the course of his life, Neill was also a supremely gifted individual. He excelled by turns as a missionary, a bishop, an ecumenist, a professor, and a prolific author, all the while travelling around the world to share his tremendous knowledge of the world Christian movement with scholars, clergy and laypersons alike. This is the first complete biography of this influential figure, and builds on Daughrity's previous work Bishop Stephen Neill: From Edinburgh to South India (Peter Lang Publications, 2008). It stands to become the authoritative word on a man who understood Christianity's changing contours better than most during the dramatic diversification that it underwent during his lifetime.